THE HISPANO-HELLENIC RELATIONSHISP DURING THE MILITARY DICTATORSHIPS OF THE GENERALS PRIMO DE RIVERA IN SPAIN AND PÁNGALOS IN GREECE (1923-1926). - Morcillo Rosillo, Matilde (Revista de Historia Social y de las Mentalidades, 2011)
This paper is an approach to the study of the Hispano-Hellenic relationships during the military dictatorships of the Primo de Rivera in Spain and Pángalos in Greece, through the Greek press, the first one, and the diplomatic Spanish correspondence, the second one. Special importance requires the role carried out by the Greek writer Nikos Kazantzakis as a special correspondent of general Pángalos to analyze the politico-economic and artistic situation of Spain, having as backdrop the political circumstances of both Greece and Spain in that moment, as well as to impel the relationships between both nations, deteriorated after the First World War.